Sharing recipes for "blendships" and optimal well-being: communicating community on healthy living blogs - Fedunchak, Aleksandra, author; Sprain, Leah, advisor; Merolla, Andy, committee member; Kwiatkowski, Lynn, committee member (Colorado State University. Libraries, 2012)
This thesis seeks to understand how the discourse on healthy living blogs can function socially, create and maintain an online community, foster a network of social support, and establish meanings of health for blog participants through performing Cultural Discourse Analysis. The four research questions that guide my analysis are: first, what is being accomplished through participation (authoring and commenting) on the sample of Healthy Living Blogs (HLBs)? What, if any, are the social functions of blogging about and commenting on healthy living for the participants? Second, does this network of healthy living blogs exemplify characteristics of a virtual community? Third, what, if any, are the key symbols used to communicate social support? And lastly, what does being "healthy" and "unhealthy" mean to the bloggers and blog participants (what are the discourses used to communicate these meanings)? In my analysis, I find that blog participants engaged in communicative action through the process of "confessing," they communicated sense of being to cultivate online personalities, and they portrayed senses of relating by referring to one another as friends, "blends," and by discussing important "blendships" (i.e., combination of the word blogger and friendship). Additionally, blog participants frequently and willingly exchanged information, provided social support, and offered advice and solutions to one another to foster connectedness, which symbolizes a sense of virtual community. Ultimately, two paradoxes became clear in that bloggers were rewarded with greater amounts of supportive comments ascribing them as strong when they shared weaknesses, and that the overt definition of health as a balance of multi-faceted features was challenged by a strong content focus on nutrition and fitness as primary tools for being "healthy." On the premise that blogging, a discursive practice, is a form of everyday communication, and thus has the ability to build trust and senses of community between individuals, this thesis analyzes how three healthy living bloggers and the blog participants that comment on the blogs, respectively, potentially function to reconceptualize what it means to be healthy.
Keywords: blogging; health blogs; ethnography of communication